Implementasi Kebijakan Layanan Pengaduan Masyarakat Melalui SP4N-LAPOR! Di Dinas Komunikasi, Informatika, Statistik Dan Persandian Provinsi Banten - Siti Apriliyaningsih; Gatot Hartoko; Eli Apud Saepudin (Universitas Serambi Mekkah, 2026)
This study aims to analyze the implementation of public complaint service policy through the National Public Service Complaint Management System–Online People's Aspirations and Complaints Service (SP4N-LAPOR!) at the Communication, Informatics, Statistics, and Encryption Office of Banten Province. The study is motivated by the importance of delivering transparent, responsive, and accountable public services through the utilization of information technology as a platform for citizens to submit aspirations and complaints. However, the implementation of SP4N-LAPOR! continues to face several challenges, including limited public participation, suboptimal coordination among regional government agencies, inadequate human resources, and uneven understanding of complaint management procedures among public officials. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The analysis of policy implementation was based on George C. Edward III's implementation theory, covering communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of SP4N-LAPOR! in Banten Province has been generally effective, supported by the availability of a digital complaint management system and inter-agency coordination. Nevertheless, further improvements are required through strengthening the capacity of public officials, expanding public awareness and outreach, enhancing institutional coordination, and optimizing the use of information technology to improve the quality, responsiveness, and accountability of public service delivery.